"The Role of Option Contracts in Reducing Derivatives Market Risk "An Empirical Study, 2000-2016 - Hassan, Abbas Fouad (Journal of Economic, Administrative and Legal Sciences, 2017)
The study aimed to identify the role of the option contract to meet the needs of investors in capital markets and measure the relationship between the hedging against investment risks and reduce financial risks so as the investor is not exposed to financial losses. The study used simple linear correlation coefficient (Pearson) to measure the strength of the relationship between the variables of the study, the simple regression model to measure the nature of the relationship between the dependent variable and the independent variables of the study.One of the most important results of the study that the option is one of the tools of hedging against financial risks and provide investors with profits. The study recommended the need to raise awareness of the role of financial and investment option in hedging and risk reduction in financial markets and encourage deal.
Keywords: Capital Markets; Options; Financial Risks; Hedging; Simple Regression; Simple Correlation; Pearson